Surveillance Patterns After Curative-Intent Colorectal Cancer Surgery in Ontario. Issue 8 (2014) - Tan, Jensen; Muir, Jennifer; Coburn, Natalie; Singh, Simron; Hodgson, David; Saskin, Refik; Kiss, Alex; Paszat, Lawrence; El-Sedfy, Abraham; Grunfeld, Eva; Earle, Craig; Law, Calvin
Abstract : BACKGROUND: Postoperative surveillance following curative-intent resection of colorectal cancer (CRC) is variably performed due to existing guideline differences and to the limited data supporting different strategies. OBJECTIVES: To examine population-based rates of surveillance imaging and endoscopy in patients in Ontario following curative-intent resection of CRC with no evidence of recurrence, as well as patient or disease factors that may predispose certain groups to more frequent versus less frequent surveillance; to provide insight to the care patients receive in the presence of conflicting guidelines, in efforts to help improve care of CRC survivors by identifying any potential underuse or overuse of particular surveillance modalities, or inequalities in access to surveillance. METHOD: A retrospective cohort study was conducted using data from the Ontario Cancer Registry and several linked databases. Ontario patients undergoing curative-intent CRC resection from 2003 to 2007 were identified, excluding patients with probable disease relapse. In the five-year period following surgery, the number of imaging and endoscopic examinations was determined. RESULTS: There were 4960 patients included in the study. Over the five-year postoperative period, the highest proportion of patients who underwent postoperative surveillance received the following number of tests for each modality examined: one to three abdominopelvic computed tomography (CT) scans (n=2073 [41.8%]); one to three abdominal ultrasounds (n=2443 [49.3%]); no chest CTs, one to three chest x-rays (n=2385 [48.1%]); and two endoscopies (n=1845 [37.2%]). Odds of not receiving any abdominopelvic imaging (CT or abdominal ultrasound) were higher in those who did not receive adjuvant chemo-therapy (OR 6.99 [95% CI 5.26 to 9.35]) or those living in certain geographical areas, but were independent of age, sex and income. Nearly all patients (n=4473 [90.2%]) underwent ≥1 endoscopy at some point during the follow-up period. CONCLUSION: In contrast to findings from similar studies in other jurisdictions, most Ontario CRC survivors receive postoperative surveillance with imaging and endoscopy, and care is equitable across sociodemographic groups, although unexplained geographical variation in practice exists and warrants further investigation.